Health Tourism—Subject of Scientific Research: A Literature Review and Cluster Analysis - Roman, Michał; Roman, Monika; Wojcieszak-Zbierska, Monika (International journal of environmental research and public health, 2022)
The purpose of this article is to identify main research areas in health tourism in scientific research. The data used in this analysis span from 2000 to 2022, was retrieved from the Web of Science database, and comprises a total of 1493 bibliometric records of publications. The paper includes both a quantitative and a qualitative analysis. The following four main research areas were identified based on the results: (1) patient satisfaction built upon trust; (2) health impacts of the destination (including the economic aspect, which plays a decisive role in choosing a tourism destination); (3) health behavior as a major part of human activity; and (4) traveling with a view to regain one’s health. Note that the limitations of this study—which mostly affect the methodological part—need to be taken into consideration. This is the consequence of the selected publication database and of the search criteria used, such as the publication year or language.